Improving Protection for Research Subjects - Steinbrook, Robert (The New England journal of medicine, 2002)
In March 1996, Hoiyan Wan, a 19-year-old nursing student and a healthy volunteer in a study at the University of Rochester, died two days after undergoing bronchoscopy as part of the study. During the procedure, she received a fatal dose of lidocaine. A report that followed a state investigation criticized the researchers, the institutional review board (IRB), and the university. 1 Wan's death led to many changes at the University of Rochester, including the establishment of training programs for investigators and an overhaul and expansion of the university's IRBs. The university's response is sometimes cited as a model for other institutions . . .